W poszukiwaniu zintegrowanej koncepcji implementacji strategii - Kubiński, Piotr (In Search of an integrated concept of strategy implementation, 2006)
The article raises, not often discussed in literature, problem of strategy implementation. I presents different concepts, ways and instruments of implementation. The author discusses the nature and concepts of strategy implementation at synopsis and incremental approach.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 94-102